Outcomes of Rhegmatogenous Retinal Detachment: Doi: 10.36351/pjo.v37i1.1073 - Riaz, Sidrah; Khan, Muhammad Tariq; Mirza, Khurram Azam (Pakistan Journal of Ophthalmology, 2020)
Purpose: To study demographic characteristics and treatment outcomes of Rhegmatogenous retinal detachment in a private Vitreo-retinal setup of Lahore. Study Design: Cross sectional Observational study. Place and Duration of Study: Private Vitreo-retinal setup, from March 2017 to April 2019. Methods: Total 102 patients with Rhegmatogenous retinal detachment (RRD) were included. Patients with retinal detachment other than RRD were excluded. Detailed history and ocular examination was performed. Type of break, procedure adopted for RRD repair and type of endo-tamponade were also recorded. These patients had either 23 G pars plana vitrectomy (PPV) or scleral buckling (SB) procedures or combined sclera buckling with PPV. Patients were followed-up for six months. Results: Out of 102 total RRD cases, 63.70% were males and 36.30%were females. Mean age was 47.44 ± 18.44. Macula was on in 48% and off in 52%. Phakic patients were 46.50%, pseudophakic 48.50% and 5.10% were aphakic. Position of break in RRD was superotemporal in 39.2%, inferotemporal in 30.4% and inferonasal in 2.9%. Total RD was observed in 27.5% patients. One or more breaks were identified in 82.4% patients and giant tear in 4.9%. Three ports 23 G PPV was done in 64.7%, PPV with IOL in 18.6%, scleral buckling in 10.8% and combined PPV + SB in 5.9% patients. The anatomical success rate was observed in 96.07%, 3.9% needed second surgery to get anatomical success in six months follow-up. Conclusion: Anatomical success rates in retinal attachment surgeries in experienced hands is comparable with more developed retinal centers of the world. Key Words: Rhegmatogenous retinal detachment, Pars plana vitrectomy, Scleral buckling, Silicon oil.